2017
DOI: 10.5539/elt.v10n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Read-aloud Instruction on Motivation and Learning Strategy among Japanese College EFL Students

Abstract: Poor English performance among Japanese college EFL students has often been explained by grammar-translation and lecture-memorization instruction. This study investigated the effectiveness of a recently designed teaching method, namely, "The read-aloud instruction package," which consists of four major activities: Slash/chunked reading practice (S/CRP), repeated read-aloud practice (RRAP), cloze test, and simultaneous read-aloud and write-out practice (SRAWOP). The study also examined how EFL college students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…The questionnaire results revealed that after the explicit reading strategy instruction, there were no significant differences in changes in students’ reported reading motivation and reading self-efficacy. These results were congruent with the observation in a number of previous studies that reading strategy intervention did not impact on students’ reading motivation and self-efficacy significantly (e.g., Antoniou & Souvignier, 2007; Lau, 2016; Lau & Chan, 2007; Shinozuka et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The questionnaire results revealed that after the explicit reading strategy instruction, there were no significant differences in changes in students’ reported reading motivation and reading self-efficacy. These results were congruent with the observation in a number of previous studies that reading strategy intervention did not impact on students’ reading motivation and self-efficacy significantly (e.g., Antoniou & Souvignier, 2007; Lau, 2016; Lau & Chan, 2007; Shinozuka et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In the L1 reading context, Guthrie et al (1996), Guthrie et al (2000) had confirmed that the concept-oriented reading instruction (CORI) could boost participants’ intrinsic motivation. Shinozuka et al (2017) study of a 3-month reading strategy instruction with 32 Japanese freshman students, however, demonstrated no significant changes in students’ motivation after the reading strategy instruction. In Shinozuka et al’s study, a modified version of reading motivation questionnaire (Narita, 1998) adapted from Gardner and Lambert’s (1972) Motivation Questionnaires Battery was used to measure learners’ motivation before and after the reading strategy instruction.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…Language learning strategies are generally defined as the EFL learner's consciously chosen tools for active, self-regulated improvement of language learning (Shinozuka, Shibata, & Mizusawa, 2017).There are a number of ways to categorize types of learning strategies (Gan, Humphreys, & Hamp-Lyon, 2004;O'Malley, Chamot, Stewner-Manzanares, Kupper, & Russo, 1985). O'Malley and Chamot (1985) divide language learning strategies into three main kinds.…”
Section: Learning Strategiesmentioning
confidence: 99%